REVIEW OF ISLAMIC LAW AND LAW NO. 1 OF 1974 AND CONSTITUTIONAL COURT DECISION NO. 46/PUU-VIII/2010 CONCERNING SIRI MARRIAGE LAW: THE POSITION OF WIVES, CHILDREN AND PROPERTY - Bakri, Syaiful; Abrori, Muhammad (Universitas Nurul Jadid, 2025)
This study discusses the position of wives, children, and property in unregistered marriages based on Islamic law, Law No. 1 of 1974, and Constitutional Court Decision No. 46/PUU-VIII/2010. The method used is a legal-normative approach with a comparative approach to Islamic legal literature and legislation. The results of the study show that according to Islamic law, unregistered marriages are valid religiously if they fulfill the pillars and requirements of marriage, but they do not have legal force because they are not registered. As a result, wives and children find it difficult to obtain legal protection for their status and civil rights, including inheritance rights and joint property. Constitutional Court Decision No. 46/PUU-VIII/2010 recognizes the civil relationship between children born out of wedlock and their biological fathers, thereby strengthening legal protection for children born from siri marriages. Therefore, marriage registration is important to ensure legal certainty for all parties.